2014
DOI: 10.7717/peerj.472
|View full text |Cite
|
Sign up to set email alerts
|

Hemigrapsus sanguineusin Long Island salt marshes: experimental evaluation of the interactions between an invasive crab and resident ecosystem engineers

Abstract: The invasive Asian shore crab, Hemigrapsus sanguineus, has recently been observed occupying salt marshes, a novel environment for this crab species. As it invades this new habitat, it is likely to interact with a number of important salt marsh species. To understand the potential effects of H. sanguineus on this ecosystem, interactions between this invasive crab and important salt marsh ecosystem engineers were examined. Laboratory experiments demonstrated competition for burrows between H. sanguineus and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This was supported by an absence of any significant difference in density, size, or sex ratio of H. sanguineus between different tidal levels at the sites included in this survey, as well as by Lohrer et al (2000), who found no tidal preference for H. sanguineus . Along with the recent spread of H. sanguineus into salt marshes (Peterson et al 2014), the lack of tidal level preference suggests a generality of habitats that could contribute to the continued success of this invasive crab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by an absence of any significant difference in density, size, or sex ratio of H. sanguineus between different tidal levels at the sites included in this survey, as well as by Lohrer et al (2000), who found no tidal preference for H. sanguineus . Along with the recent spread of H. sanguineus into salt marshes (Peterson et al 2014), the lack of tidal level preference suggests a generality of habitats that could contribute to the continued success of this invasive crab.…”
Section: Discussionmentioning
confidence: 99%
“…Asian shore crabs have also caused declines in populations of barnacles, spirorbid worms, littorine snails, mud crabs, and fiddler crabs, which they have recently begun to outcompete for burrows in salt marshes as they move into this new habitat (Tyrrell et al 2006; Kraemer et al 2007; Peterson et al 2014). Asian shore crabs can also consume juvenile lobsters, which they have the additional potential to compete with in rocky cobble habitats (Demeo and Riley 2006; Lord and Dalvano 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It prefers rocky substrate to sand and settles in the presence of conspecific adult olfactory cues ( Lohrer et al, 2000 ; Steinberg, Epifanio & Andon, 2007 ; Hudson, 2011 ; Rasch & O’Connor, 2012 ). In the intertidal zone, predation occurs from both terrestrial and marine sources, which makes H. sanguineus a vigorous intertidal competitor for space and shelter due to its avoidance of risk during shelter choice and aggression toward smaller interspecific competitors ( Jones & Shulman, 2008 ; Wieters et al, 2009 ; Rasch & O’Connor, 2012 ; Peterson et al, 2014 ). As such, we wanted to see if the presence of this species impacted the use of shelter by LIS community members in the field.…”
Section: Introductionmentioning
confidence: 99%
“…This exploitative competition exposes C. maenas to predators as well as harsher abiotic conditions. H. sanguineus appears to be much less plastic in its tolerance for alternative habitats, though recent observations have found them in marsh environments (Peterson et al 2014). …”
mentioning
confidence: 99%